S116 Urge-to-cough intensity in chronic cough patients compared to asthmatics and healthy controls. (16th November 2010) - Young, E C; Sumner, H; Kelsall, A; Woodcock, A A; Smith, J A
Abstract : Background: Healthy subjects inhaling increasing doses of capsaicin perceive an urge-to-cough (UTC) prior to initiating coughing. We compared subjective ratings of UTC intensity following inhalation of capsaicin in patients with chronic cough (CC), asthma (A) and healthy controls (HC). Methods: A double-blind, randomised block design, capsaicin cough challenge was performed using single-breath inhalations, separated by 1 min, through a dosimeter (inspiratory flow rate limited). Seven individually pre-determined doses (0.48–1000 μMol; maximum dose inducing an average of at least five coughs) and one placebo dose were administered four times each, in four individually randomised blocks (Davenport et al ), to reduce the bias associated with subjective UTC ratings. After each inhalation, UTC was rated on a modified Borg scale (0–10) and number of coughs in the first 15 s was recorded. Using Generalised Estimating Equations (GEE), we explored the effect of group and gender on average UTC intensity and average cough responses to increasing concentrations of capsaicin. Results: We studied 20 treatment resistant CC, 18 stable mild/moderate A and 20 HC subjects, matched for gender (M:F 10:10, 9:9, 10:10, respectively), age [mean (±SD) 57.1 years (±15.7), 51.7 years (±13.5), 58.8 years (±13.5); p=0.17], and lung function [3.02L (±0.98), 2.96L (±1.10), 3.20L (±0.99); p=0.72]. CC had significantly greater UTC intensity (p=0.006, see Abstract S116 Figure 1 ) and cough responses (p=0.002) compared to HC. Females had significantly greater UTC (p=0.001) and cough responses (p<0.001) compared to males. There was no significant difference in UTC intensity (p=0.449) or cough responses (p=0.997) between A and HC. Conclusions: In a randomised double-blind capsaicin cough challenge: Chronic cough patients perceive a more intense UTC sensation and also demonstrate a greater magnitude of cough response than healthy controls. Females perceive a more intense UTC sensation than males. These findings suggest both a heightened sensory experience in addition to an excessive motor response in patients with chronic cough. This data could be explained by sensitisation of afferent pathways (ie, peripheral and/or central sensitisation) but also by impaired inhibitory control mechanisms.